DISPUTE RESOLUTION ARRANGEMENTS IN ISLAMIC BUSINESS PRACTICES - Sibarani, Fauzi Anshari (Inspiring Law Journal, 2024)
Dispute in the Indonesian Dictionary means opposition or conflict. Conflict means opposition or conflict between people, groups, or organizations against one problem object. Conflict or conflict between individuals or groups who have the same relationship or interest in an object of ownership causes legal consequences between each other. Conflict or dispute is a situation and condition when people experience factual disputes or disputes in their perceptions only. In terms of terminology, a dispute is a conflict between two or more parties that originates from differences in perception about an interest or right of choice, resulting in legal consequences for both. In a dispute, the parties can be subject to legal sanctions against one of them. In short,